Evaluation of General Bioactive Phytochemicals, Antioxidant Activity, and Organoleptic Properties of Ficus racemosa L. as Herbal Tea - Novia Suryani; Yuli Kusuma Dewi; Baiq Rauhil Hidayanti (Postgraduate, University of Mataram, 2025)
Ficus rasemosa L. (FR), commonly known as a fig tree in Asia, is traditionally consumed in Lombok and recognized for its medicinal due to its phenolic compounds, as general bioactive compounds FR contain, have benefits such as being antidiabetic properties. Despite its ethnobotanical significance, limited studies have explored the development of FR fruits as a functional herbal tea, particularly concerning processing variables such as drying temperatures. This study evaluated the effects of three drying temperatures—50 oC (T1), 60 oC (T2), and 70 oC (T3)—on the total flavonoid content (TFC), total phenolic content (TPC), antioxidant activity (DPPH free radical scavenging assay), and organoleptic properties of FR herbal tea. The TFC, TPC, and DPPH assay were quantified using UV-VIS spectrophotometry. The highest TFC (1.96 g QE/g) and TPC (0.36 g GAE/g) were observed at 50 oC, while the strongest antioxidant activity with the lowest IC50 of 192.27 ppm occurred at 60 oC. Sensory evaluation showed the teas dried at 60 and 70oC were more acceptable, particularly in terms of color and overall preference. These results suggest that drying at 60 oC offers an optimal balance between phytochemical, antioxidant activity, and sensory quality, highlighting the potential of RF fruit as functional herbal tea.